2006
DOI: 10.1161/circulationaha.105.609008
|View full text |Cite
|
Sign up to set email alerts
|

An Abnormal Mitochondrial–Hypoxia Inducible Factor-1α–Kv Channel Pathway Disrupts Oxygen Sensing and Triggers Pulmonary Arterial Hypertension in Fawn Hooded Rats

Abstract: Background-The cause of pulmonary arterial hypertension (PAH) was investigated in humans and fawn hooded rats (FHR), a spontaneously pulmonary hypertensive strain. Methods and Results-Serial Doppler echocardiograms and cardiac catheterizations were performed in FHR and FHR/BN1, a consomic control that is genetically identical except for introgression of chromosome 1. PAH began after 20 weeks of age, causing death by Ϸ60 weeks. FHR/BN1 did not develop PAH. FHR pulmonary arterial smooth muscle cells (PASMCs) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
569
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(599 citation statements)
references
References 53 publications
26
569
2
2
Order By: Relevance
“…An extension of this paradigm is the evidence that the pulmonary vascular remodeling in severe PH involves elements of abnormal angiogenesis [40], and it resembles that seen in neoplastic cells [41]. HIF-1α controls several features involved in angiogenesis and cancer cell growth, including mitochondria function, which have been validated recently in studies of experimental PH [42]. Mitochondria of PASMCs are different from their systemic counterpart, as they have lower respiratory rates, are more depolarized, have more manganese superoxide dismutase (MnSOD), and produce more hydrogen peroxide [43].…”
Section: Hypoxia Signaling In the Lungmentioning
confidence: 96%
“…An extension of this paradigm is the evidence that the pulmonary vascular remodeling in severe PH involves elements of abnormal angiogenesis [40], and it resembles that seen in neoplastic cells [41]. HIF-1α controls several features involved in angiogenesis and cancer cell growth, including mitochondria function, which have been validated recently in studies of experimental PH [42]. Mitochondria of PASMCs are different from their systemic counterpart, as they have lower respiratory rates, are more depolarized, have more manganese superoxide dismutase (MnSOD), and produce more hydrogen peroxide [43].…”
Section: Hypoxia Signaling In the Lungmentioning
confidence: 96%
“…While oxidative stress could contribute to depleting sGC heme, it is not currently known if heme levels in smooth muscle also decrease as a result of increased HO-1 activity and/or a reduced level of heme biosynthesis. Mitochondrial dysfunction is seen in many vascular diseases, including pulmonary hypertension (5), and this could be hypothesized to be a factor in impairing the biosynthesis of heme by this organelle. While it has been observed that a key beneficial effects of HO-1 induction on reversing vascular dysfunction in vivo can originate from its lowering of superoxide levels (34), sGC heme depletion by HO-1 could a factor where vascular disease processes have elevated HO-1 levels and impaired vascular regulation by the NO-sGC system is observed.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired glucose metabolism has been described in SMCs and ECs in both humans and rodent models of PAH (Bonnet et al, 2006;Fijalkowska et al, 2010;Xu et al, 2007). There are many pathological implications of this phenotype; 1) suppressed apoptosis, 2) impaired signaling of pro-proliferative downstream targets (ie.…”
Section: Metabolic Alterations In Pulmonary Vascular Cellsmentioning
confidence: 99%
“…The use of metabolic modulator, DCA, for treatment of PAH has shown promising results in animal models (McMurtry et al, 2004;Bonnet et al, 2006). Additionally, DCA has been used as a therapy for metabolic disease and lactic acidosis, which lowers the barrier for clinical trials and translation into PAH patients Michelakis et al, 2013).…”
Section: Metabolic Alterations In Pulmonary Vascular Cellsmentioning
confidence: 99%